2008
DOI: 10.1017/s1751731108002140
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of conversion of metabolisable protein into milk true protein over a range of metabolisable protein intakes

Abstract: The aim of this work was to test the robustness of the 0.68 estimate of the efficiency of conversion of metabolisable protein into true milk protein (Agriculture and Food Research Council (AFRC), 1993) for protein-limiting diets and to determine whether a different value is appropriate for practical rationing. Seventy-two multiparous cows were blocked on the basis of milk energy output per unit of dry matter intake (DMI), and allocated at random to one of four treatments. Treatments supplied metabolisable ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 11 publications
8
29
4
Order By: Relevance
“…Newbold (1994) discussed the need for different optimal ratios of MP : ME at different levels of ME intake. Metcalf et al (2008) reported responses to MP above optimal MP : ME ratios, but with decreasing efficiency of MP utilization. 7.…”
Section: Efficiency and Dietary Proteinmentioning
confidence: 97%
See 2 more Smart Citations
“…Newbold (1994) discussed the need for different optimal ratios of MP : ME at different levels of ME intake. Metcalf et al (2008) reported responses to MP above optimal MP : ME ratios, but with decreasing efficiency of MP utilization. 7.…”
Section: Efficiency and Dietary Proteinmentioning
confidence: 97%
“…As the efficiency of conversion of MP and that of metabolisable amino acids into milk TP declines with both increasing supply of MP (Metcalf et al, 2008) and with Met and Lys (Vyas and Erdman, 2009), it follows that production responses to rumen protected forms of specific amino acids may increase at lower dietary protein levels so long as dietary energy intake and other amino acids do not become rate limiting. Most major protein sources contain less Met and Lys than does MCP, so that the proportion of these limiting amino acids in duodenal digesta decline at higher levels of dietary CP (Robinson, 2010).…”
Section: Cp and Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Van Amburgh et al (2009) stated that the first step in balancing for AA is to ensure that the model is capable of predicting MP-allowable milk with good accuracy and precision. In addition to the challenges of predicting MP and AA flows to the small intestine (NRC, 2001;Van Amburgh et al, 2009) and their intestinal digestibility (Boucher et al, 2009), the efficiency of use of the MP for lactation decreased from 77 to 50% as MP supply increased (Metcalf et al, 2008). Ruiz et al (2002) reported that with N-deficient diets, using an MP for lactation efficiency of 75% resulted in no bias with CNCPS prediction of milk production.…”
Section: Lactating Dairy Cowsmentioning
confidence: 99%
“…One aspect of nutrient partitioning, the relation between changes in nutrient supply and milk production and composition, has received a lot of attention. In particular, the effects of changes in either metabolizable protein (MP) (Vérité et al, 1987;Metcalf et al, 2008) or net energy (Coulon and Rémond, 1991) on milk outputs have been largely characterized. However, it is still unclear how to quantitatively combine the effects of changes in net energy and MP, including possible interactions between them, for predicting milk yield and milk composition responses.…”
Section: Introductionmentioning
confidence: 99%